Knowledge domain and trends in treatment-resistant schizophrenia (TRS) research based on CiteSpace bibliometrics analysis - Cai, Haipeng; Du, Ruonan; Zhang, Jianyi; Wang, Xin; Li, Wei; Yang, Kebing; Wang, Zhiren (Frontiers in Pharmacology, 2024)
Background: Although the number of studies on treatment-resistant schizophrenia (TRS) has been increasing, the global research hotspots and future research trends have not yet been established.Objective: This study identify the hotspots of TRS research and predict future research trends using a bibliometric analysis.The Web of Science Core Collection was searched using the keyword "TRS", econometric and co-occurrence analyses were conducted using CiteSpace and VOSviewer software, and the results were visualised. PRISMA reporting guidelines were used for this study.Results: In total, 912 publications were included in the analysis. The number of publications on TRS has shown an increasing trend over the past 20 years. The United States and University of London were the countries and institutions with the highest total number of publications, respectively. Schizophrenia Research was the journal with the highest number of articles.American Journal of Psychiatry was the most cited journal. Based on the results of this analysis, cognitive impairment, clozapine-resistant schizophrenia, early-onset schizophrenia, and early recognition of TRS will be hotspots for future research in this field.Conclusions: There has been an upward trend in the number of publications on TRS each year.However, issues such as how to use antipsychotics more efficiently to treat TRS and how to predict the emergence of TRS as early as possible are still in urgent need of research and are current challenges for clinicians. The results of this study not only predict and analyse future research hotspots but also help researchers identify appropriate research directions and partners.